PROFIL SISWA BERKEBUTUHAN KHUSUS DI SD N 20 MATARAM - Aisa Nikmah Rahmatih; Ketut Sri Kusuma Wardani; Ni Luh Putu Nina Sri Warthini; Fitri Puji Astria; Asri Fauzi (PROGRES PENDIDIKAN, 2020)
Children with special needs are someone who is experiencing growth problems and developmental obstacles which in the education service must be provided by the government without exception. Inclusive education is the provision of education that provides opportunities for all students who have the potential intelligence and / or special talents to participate in learning in one environment together with students in general. This study provides an overview of the profile and characteristics of students with special needs in the SD N 20 Mataram designated as research providers using a qualitative approach. Data collection methods by interview, observation and documentation were analyzed to answer the questions of this study. The results of this study are that there are several types of students with special needs including down syndrome, autism, ADHD (hyperactivity), dyslexia, slow learning, learning difficulties, mental retardation, deafness spread across grades 1 through 6. Learning for students with special needs is carried out together with other students with some modifications, adjusting the abilities of each student with special needs.